A missed encounter
1 online resource.
Keywords: "This book marks a missed encounter between two of the most influential Marxists thinkers of our age, Walter Benjamin, and Antonio Gramsci, studied here for the first-time side by side. Benjamin and Gramsci were contemporaries, whose births and deaths took place within a few years of each other in Western Europe in the first half of the 20th century. Two Marxists sui generis, they radically changed Marxism's themes and vocabulary, profoundly influencing the most significant analyses and debates. At a time in which Marxism was considered to be outdated and in crisis, both Gramsci's and Benjamin's thought provided resources for its renewal: particularly in post-colonial studies for Gramsci and in new media studies for Benjamin. Both were victims of fascism, on the threshold of the catastrophe of the Second World War. These two philosophers' posthumous fortune depended on the transmission of their thought, which was first entrusted to friends and comrades, and then to entire generations of scholars from a wide range of disciplines. Editors, Dario Gentili, Elettra Stimilli, Gabriele Guerra explore with leading voices on Benjamin and Gramsci the most relevant and topical issues today. An indispensable new perspective in Marxism for students and researchers alike"--